Implementation Of Rubber Ball Grasp ExercisesIn Patients With Physical Mobility Impairment - azka, Nia diyah; Widodo, Wasis; Wulansari, Novia (Development Nursing Research, 2026)
Abstract Background: Nervous System Disorders are a disease that affects the entire nervous system, where this condition can affect neurons or tracts of the central nervous system in the spinal cord or the entire brain or cerebrum (cortex), cerebellum. In addition, conditions that affect the peripheral nervous system involve the cranial nerves or nuclei, spinal plexuses, peripheral nerves, nerve roots, autonomic nerves, neuromuscular junctions, and muscles, (World Health Organization). Based on Roy's adaptation theory that nerve function: Neurological connections are an integral part of a person's coping mechanism regulator. has a function to control and coordinate body movements, awareness and good cognitive emotional processes to regulate the activity of the body's organs. Application of rubber ball grip exercise techniques is to increase muscle strength in stroke patients Methods: Case study design, with stroke patient subjects, observation sheet data collection instruments, standard operating procedures (SOP). in performing rubber ball grip exercises. Results: Researchers showed that after implementing the ball grip exercise technique, there was an increase in muscle strength in stroke patients. Mr. Y was only able to do 2 cycles. Mrs. C was able to do ball grip exercise therapy actively and could do it independently with 5 cycles. proven in respondents 1 and 2 can increase muscle strength in Mrs. c muscle strength to 5 and Mr. Y muscle strength to 3 Conclusions: the application of rubber ball grip exercises to increase muscle strength and nursing function in the concept of Roy's adaptation is a neurological relationship is an integral part of a person's coping mechanism regulator. has a function to control and coordinate body movements, awareness and good cognitive emotional processes to regulate the activity of body organs the function of nurses to make patients independent after providing education or therapeutic actions recommended for patients with physical mobility disorders.